Intrauterine undernutrition and programming as a new risk of cardiovascular disease in later life - Szitányi, P; Janda, J; Poledne, R (Physiological research, 2003)
It is believed that atherogenesis is a multifactorial process, which could already start in utero. Development of atherosclerosis progresses over decades and leads to the cardiovascular morbidity and mortality in adulthood. At present, we have no exact explanation for all the risk factors acting in the pathogenesis of atherosclerosis. This review should provide an overview about the possible role of intrauterine undernutrition in the development of risk factors for cardiovascular disease. Intrauterine undernutrition leads to changes in fetal growth and metabolism and programs later development of some of these risk factors. A number of experimental and human studies indicates that hypertension as well as impaired cholesterol and glucose metabolism are affected by intrauterine growth. Intrauterine undernutrition plays an important role and acts synergistically with numerous genetic and environmental factors in the development of atherosclerosis. There is evidence that undernutrition of the fetus has permanent effects on the health status of human individuals.
Keywords: dospělí; Female; Placental Insufficiency; novorozenec; Birth Weight; Adult; ženské pohlaví; lidé; Arteriosclerosis; Infant, Newborn; placentární insuficience; porodní hmotnost; těhotenství; zpožděný efekt prenatální expozice; Risk Factors; Cardiovascular Diseases; Prenatal Exposure Delayed Effects; rizikové faktory; kardiovaskulární nemoci; arterioskleróza; Pregnancy; Humans